Tear IgE point-of-care testing for differentiating type I and type IV allergic conjunctivitis - Shang, Xumin; Zhang, Yiqiu; Luo, Shunrong; Liu, Miaomiao; Li, Hanqiao; Fang, Xie; Xie, Zhiwen; Xiao, Xianwen; Yang, Zhengwei; Lin, Yuan; Wu, Huping (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to evaluate the diagnostic utility of point-of-care tear immunoglobulin E (IgE) testing in distinguishing between type I and type IV allergic conjunctivitis (AC), and to explore tailored treatment strategies.MethodsA total of 254 patients with perennial AC at Xiamen Eye Center were enrolled. Clinical data, including age, sex, symptoms, and signs, were collected. Tear total IgE was measured using the i-ImmunDx™ platform. Univariate and multivariate logistic regression analyses, along with ROC curve analysis, were used to assess the discriminative value of tear IgE and clinical parameters for AC subtypes.ResultsThe mean patient age was 14.11 ± 12.46 years; 182 were male. Mean conjunctivitis score was 4.09 ± 1.51, and mean tear IgE was 7.73 ± 16.76 IU/mL. Tear IgE levels negatively correlated with age (p < 0.05), and positively with conjunctival secretion, papillary hyperplasia, and conjunctivitis scores (p < 0.05). Univariate analysis showed age, tear IgE, and papillae were significantly associated with type IV AC. Multivariate analysis identified tear IgE, conjunctival papillae, and conjunctivitis score as independent predictors. ROC analysis showed an AUC of 0.896 for tear IgE (cut-off = 5.57 IU/mL; sensitivity 89.00%, specificity 77.78%). A combined model (IgE + papillae + score) improved AUC to 0.912, with sensitivity of 81.50% and specificity of 88.89%.ConclusionTear IgE effectively differentiates AC subtypes and correlates with disease severity. Patients with low IgE levels, indicative of type IV hypersensitivity, benefit from individualized anti-inflammatory therapies, supporting its role in personalized management.